ISTI’ADZAH PERSPEKTIF TAFSIR SUFI (Studi Tafsir Sufistik Ruh Al-Ma’ani Terhadap Ayat-Ayat Isti’adzah) - Muhammad Ahsanul; Lukman Nul Hakim; Almunadi (Penerbit Hellow Pustaka, 2025)
Isti'adzah is a form of request from a servant to his Lord for protection, as in the Qur'an, Allah teaches his lovers to do Isti'adzah. In connection with the phenomenon that has occurred recently, where many people say isti'adzah but it is only a formality without understanding the meaning behind it. So, this paper contains an analysis of Ruh Al-Ma'ani's interpretation of isti'adzah verses in order to reveal the true meaning of isti'adzah. This article is qualitative in nature and the purpose of this research is that the isti'adzah uttered has an impact on the personality of a servant, especially the people around him. The results of this research are that in order to realize true quality isti'adzah, it is necessary to raise awareness of several characteristics that a servant must have, namely, taqwa, taddzakkur, tawakal, sincerity, and tawadhu'.